A Health game as an intervention to support tobacco-related health literacy among early adolescents - Parisod, Heidi (fi=Turun yliopisto|en=University of Turku|, 2018)
The aim of this study was to develop and evaluate the feasibility of a health game intervention supporting tobacco-related health literacy in 10 to 13-year-old early adolescents. The study had two phases. During the development phase, we explored the determinants of tobacco-related health literacy with a qualitative descriptive study with early adolescents (n=39, focus groups, data analyzed using thematic analysis). We also conducted a review of reviews (n=15, narrative synthesis) of existing evidence on health games among children and adolescents. Furthermore, we explored the views of (n=39, focus groups and n=83, online questionnaire, thematic analysis) and collected feedback from adolescents (n=10+44 questionnaires, statistical analysis) while producing a health game called Fume. In the second phase, we evaluated feasibility (demand, acceptability, short-term effectiveness) of Fume using validated instruments, questionnaires and by tracking its actual use. We conducted the study with 151 early adolescents using a single-blind, three-armed cluster randomized design. The McNemar, Fisher exact, and non-parametric tests were used to test differences within and between groups. The results gathered during the development phase suggest that supporting tobacco-related health literacy among early adolescents requires being aware of the multidimensional nature of the determining factors, and paying attention to the mediating role of the interpretation process of health messages. Based on existing literature health games hold potential among children and adolescents, but further research is needed. The adolescent participants pointed several aspects regarding the acceptability of Fume during its development process, including the game’s positive approach to tobacco non-use, and its high-quality graphics. The feasibility study with the game showed that, compared to a non-gamified website, there was a higher usage rate for Fume during the two-week study period (P ≤ 0.001 for all the values) as well as greater interest in Fume (P ≤ 0.001). The opinions of adolescents about the interventions did not differ in a statistically significant way. Favorable changes were found within the Fume group regarding positive (P=0.002) and negative (P=0.02) smoking outcome expectations and attitudes towards cigarette smoking (P=0.01). We did not find statistically significant differences in the changes of the theory-based determinants of tobacco-related health literacy between the Fume, website and control groups. The gathered results highlight several aspects of tobacco-related health literacy as well as of health games. Fume was found to be more feasible among early adolescents than the non-gamified website, but there is still room for improvement.

Terveyspeli tupakkaan liittyvää terveydenlukutaitoa tukevana interventiona varhaisnuorilla Tämän tutkimuksen tarkoituksena oli kehittää ja arvioida terveyspeliä tupakkaan liittyvää terveydenlukutaitoa tukevana interventiona 10–13 -vuotiailla varhaisnuorilla. Tutkimus toteutettiin kaksivaiheisena. Kehittämisvaiheessa tarkastelimme varhaisnuorten (n=39, fokusryhmähaastattelut) näkökulmasta tupakkaan liittyvää terveydenlukutaitoa määrittäviä tekijöitä laadullisella kuvailevalla tutkimuksella. Koostimme yhteenvedon kirjallisuuskatsauksissa (n=15) esitetystä tutkimusnäytöstä koskien terveyspelejä lasten ja nuorten terveyden edistämisen menetelmänä. Lisäksi tarkastelimme nuorten näkemyksiä (n=39, fokusryhmähaastattelu ja n=83, kysely, temaattinen analyysi) ja keräsimme nuorilta palautetta (n=10+44 kyselyt, tilastolliset analyysimenetelmät) terveyspelin nimeltä Fume kehitysprosessin aikana. Tutkimuksen toisessa vaiheessa arvioimme Fumen soveltuvuutta (käyttö, hyväksyntä, lyhytaikainen vaikuttavuus) terveysohjauksen menetelmänä. Osatutkimus toteutettiin ryppäittäin satunnaistetulla, kokeellisella tutkimusasetelmalla. Tähän osatutkimukseen osallistui 151 varhaisnuorta. McNemar, Fisher´s exact ja ei-parametrisiä testejä käytettiin ryhmien välisten ja sisäisten erojen analysointiin. Kehittämisvaiheen tulosten perusteella tupakkaan liittyvän terveydenlukutaidon tukeminen edellyttää terveydenlukutaitoa määrittävien tekijöiden monimuotoisuuden ja terveysviestien tulkintaprosessin roolin huomioimista. Terveyspelit osoittautuivat aiemman kirjallisuuden perusteella potentiaalisiksi lapsilla ja nuorilla, mutta tutkimusta tarvitaan lisää. Nuorten näkemykset toivat esille, että Fumen kehittämisessä huomiota tulee kiinnittää muun muassa tupakoimattomuuden positiivisten puolien korostamiseen ja korkealaatuisiin peligrafiikoihin. Soveltuvuustutkimuksessa kahden viikon ajanjaksona Fumen käyttö (P ≤ 0.001 kaikille arvioille) ja nuorten kiinnostus Fumea kohtaan (P ≤ 0.001) olivat suurempaa verrattuna eipelillistettyyn internetsivustoon. Varhaisnuorten mielipiteet interventioista eivät eronneet toisistaan tilastollisesti merkitsevästi. Havaitsimme myönteisiä muutoksia Fumea käyttäneessä ryhmässä seuraavissa muuttujissa: positiiviset (P=0.002) ja negatiiviset (P=0.02) savukkeisiin liittyvät mielikuvat ja asenteet savukkeiden polttamista kohtaan (P=0.01). Emme havainneet tilastollisesti merkitseviä eroja tapahtuneissa muutoksissa Fume-, internetsivusto- ja kontrolliryhmien välillä. Tutkimus tuotti uutta tietoa tupakkaan liittyvän terveydenlukutaidon tukemisesta ja terveyspeleistä. Tutkimus osoitti, että Fume on soveltuvampi interventio varhaisnuorilla kuin ei-pelillistetty internetsivusto, mutta peli vaatii jatkokehitystä.